17Popular Culture. (18th September 2018) - Potts, Tracey
Abstract: This year's chapter focuses upon the sights, sounds, shadows, and apparitions of modernity, in books mainly published in 2017. Beginning with popular music before moving on to a tour through the bright lights of the twentieth century and ending with a ghostly tale of a talking mongoose, the aim is to illuminate titles that place a premium upon new ways of seeing what have come to be perceived as standard features of pop culture. In particular, studies that provide attentive archival accounts of phenomena that tend to lack academic appreciation are foregrounded: elements found especially in American popular culture—the blinding spectacle, the seemingly formulaic jingle of commercial music—are re-examined against the enduring presuppositions of homogeneity, flatness, and sameness that have long tended to accompany apprehensions of the popular.